Entrepreneurship Mentoring Using a Business Model Cloud Kitchen in Vocational High Schools - Fifiyanti, Debby; Romadayanti, Chintia; Wulandari, Vivin; Hamidah, Rahmah; Nathasya, Nurvia; Sari, Luciana Lidya; Suhendar, Asep (TAAWUN, 2025)
Introducing the cloud kitchen concept to these vocational high school students aims to boost their competence by improving knowledge, fostering familiarity and understanding, and developing curriculum. It also seeks to shape an entrepreneurial mindset and increase their interest in entrepreneurship through the Cloud Kitchen business model. The program's methodology involved lectures and discussions. It began with a pre-test to gauge students' initial knowledge, familiarity, and understanding, concluding with a post-test to measure the activity's effectiveness. The pre-test results revealed that students' knowledge of the cloud kitchen business was minimal, at 19.8%. However, the post-test showed a significant increase in their knowledge, reaching 90.5%. The primary hurdles faced by SMK Ethika students when embarking on entrepreneurship were the need for substantial initial capital without its availability, and the fear of launching new businesses due to a lack of understanding of easily manageable business types. The cloud kitchen business model is well-suited for implementation, as it requires lower capital and offers a great opportunity to start a culinary business by leveraging digital technology. This activity provides a tangible contribution to the community, particularly the vocational education sector, by enhancing students' capacity and readiness to participate in the digital economy. The direct impacts include increased knowledge, improved mental preparedness, and business inspiration for students to begin developing independent digital culinary businesses.